Incidence and Risk Factors Associated with Blood Culture Proven Neonatal Sepsis - Yadav, Nikita Singh; Yadav, Pranav Kumar; Kasarla, Rajeshwar Reddy; Parajuli, Pramila (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION Neonatal sepsis (sepsis neonatorum) is a clinical syndrome resulting from the pathophysiologic effects of local or systemic infection. This is a major cause of morbidity and mortality around the world affecting newborns up to one month of age with clinical symptoms and positive blood cultures. This study aimed at examining the risk factors of neonatal sepsis at pediatric tertiary care hospital. MATERIAL AND METHODS This was a hospital based cross-sectional case control study conducted among 350 neonates admitted within April to September 2015 at the Kanti Children’s Hospital, Kathmandu Nepal. Cases were neonates who had sepsis and controls were neonates who did not have sepsis with their index mothers. CRP screening tests and blood culture was performed. Data were entered using the SPSS (Version 22). Bivariate and multivariate logistic regression was used to determine the risk of neonatal sepsis. RESULTS A total of 59 (17%) neonates who had sepsis (cases) with their index mothers’ and 291 (83%) neonates who had no sepsis (controls) with their index mothers were enrolled. Maternal factors that predicted the occurrence of sepsis among neonates were parity (p<0.027), mode of delivery (p<0.001) and PROM (p<0.001). Neonatal risk factors which predicted the occurrence of sepsis were duration of stay in the facility (p<0.001) and neonatal age on admission (p<0.001). CONCLUSION The study found both maternal and neonatal factors to have a strong association with the risk of developing neonatal sepsis. Encouraging maternal antenatal care utilization would help identify the risk factors during prenatal and postnatal care and appropriate interventions implemented to reduce the likelihood of the neonate developing sepsis.